The Relationship Between Ownership Structure And Earning Management Practice: The Conceptual Framework - Ali Hassan Ibraheem Aljadba; Norhaziah Nawai; Nur Hidayah Laili (International Research Centre of Islamic Economics and Finance (IRCIEF), 2024)
Non-Indexed Publication